Use of Mometasone furoate in prolonged treatment of experimental spinal cord injury in mice: A comparative study of three different glucocorticoids. (September 2015) - Galuppo, Maria; Rossi, Antonietta; Giacoppo, Sabrina; Pace, Simona; Bramanti, Placido; Sautebin, Lidia; Mazzon, Emanuela
Graphical abstract: Abstract: Traumatic spinal cord injury (SCI) represents one of the most disabling injuries of the human body causing temporary or permanent sensory and/or motor system deficit, particularly hind limb locomotor function impairment. At present, steroidal inflammatory drugs, in particular methylprednisolone sodium succinate (MPSS) are the first line choice treatment of acute SCI. Despite progress in pharmacological, surgical and rehabilitative treatment approaches, SCI still remains a very complex medical and psychological challenge, with no curative therapy available. The aim of the present study was to compare the efficacy of MPSS in respect to other GCs such as dexamethasone (Dex) and mometasone furoate (MF) in an in vitro suitable model of LPS-induced inflammation in J774 cells as well as in an in vivo experimental mouse SCI (compression model). In both the in vitro and in vivo experiments, MF resulted surprisingly more potent than Dex and MPSS. In detail, mice sacrificed seven days after induction of SCI trauma resulted not only in tissue damage, cellular infiltration, fibrosis, astrocyte activation, iNOS expression, extracellular signal regulated kinase 1/2 phosphorylation in injured tissue, poly (ADP-ribose) polymerase 1 (PARP-1) activation but also apoptosis (Bax and Bcl-2 expression). All three GCs demonstrated the ability to modulate inflammatory, oxidative as well as apoptotic pathways, but MF demonstrated the best efficacy, while Dex and MPSS showed alternative potency with a different degree of protection. Therefore, we can conclude that MF is the best candidate for post-traumatic chronic treatment, since it ameliorates different molecular pathways involved in the damage's propagation to the surrounding areas of the injured spinal cord.